Digenic disease causing variants in a patient with severe nephrocalcinosis - Caitlin Pollock; Robert Geraghty; Holly Mabillard; John A. Sayer (Journal of Rare Diseases, 2026)
Abstract Background Nephrocalcinosis and cystinuria are two distinct kidney disorders. Nephrocalcinosis is the abnormal, generalised deposition of calcium salts, primarily calcium phosphate or calcium oxalate, within the kidney's parenchyma, and has multiple causes including metabolic disorders, monogenic kidney diseases and medications. Cystinuria, resulting from pathogenic variants in SLC3A1 or SLC7A9 which impair amino acid reabsorption in the proximal convoluted tubule leads to cystinuria and predisposes to cystine stone formation. Case Here we describe a patient with recurrent episodes of renal colic from the age of 17 years and the formation of calcium containing kidney stones as well as medullary nephrocalcinosis. Biochemical investigations revealed evidence of mild hypophosphatemia and cystinuria. Genetic screening identified a heterozygous likely pathogenic variant in SLC34A3 consistent with the kidney stones and nephrocalcinosis as well as a heterozygous likely pathogenic variant in SLC7A9 consistent with the cystinuria phenotype. Genetic testing of available relatives identified several additional family members carrying one or more of these variants, enabling diagnosis, early risk stratification and counselling. Conclusions This case highlights the rare co-occurrence of medullary nephrocalcinosis and cystinuria secondary to two heterozygous genetic variants. It demonstrates the role of genetic screening in patients with kidney stone disease phenotypes and the correlation of clinical and biochemical phenotypes with genetic findings. Identification of these variants facilitated personalised management and screening of at-risk relatives.